ENVIRONMENTAL ETHICS AND SOCIAL PRACTICES OF WASTE MANAGEMENT: A STUDY IN KENDARI CITY - Muhammad Obie (PT. Jurnal Center Indonesia Publisher, 2026)
Waste management has become one of the most persistent environmental challenges confronting rapidly growing urban areas in Indonesia. While previous studies have primarily explained waste management through technical infrastructure, environmental awareness, or public policy, relatively little attention has been given to the interaction between environmental ethics and everyday social practices in shaping environmental behaviour. This study aims to examine how environmental ethics are translated into community waste management practices in Kendari City from the perspective of environmental sociology. A qualitative case study approach was employed using field observations, semi-structured interviews with 30 informants representing community members, religious leaders, community leaders, sanitation workers, and officials from the Kendari City Environmental Agency, as well as document analysis. The data were analysed using thematic analysis and interpreted through the analytical perspectives of Environmental Sociology, Social Practice Theory, Public Sphere Theory, and Political Ecology. The findings reveal that environmental ethics constitute an important normative foundation for environmental responsibility; however, their implementation in everyday waste management practices is mediated by socially embedded habitus, community values, institutional capacity, public discourse, and local governance. Waste management behaviour is therefore shaped not only by individual awareness but also by continuous interactions among social norms, institutional arrangements, and collective practices. The study concludes that sustainable urban waste management requires integrated approaches combining environmental ethics, community participation, participatory governance, and institutional collaboration. By integrating environmental ethics with environmental sociology, this study contributes to a broader understanding of the social dimensions of urban waste management and offers practical insights for strengthening community-based environmental governance in Indonesia.